Entomopathogenic nematodes (Rhabditida: Heterorhabditidae and Steinernematidae) screening for lesser mealworm Alphitobius diaperinus (Coleoptera: Tenebrionidae) control - ALVES, VIVIANE S.; M. J. DE O. NEVES, PEDRO; ALVES, LUIS F. A.; MOINO Jr, ALCIDES; HOLZ, NICOLE (Revista Colombiana de Entomología, 2012)
Alphitobius diaperinus (Coleoptera: Tenebrionidae), an important poultry insect pest, is difficult because of the insect’s behavior and biology and the restrictions for the used of synthetic insecticides. So, entomopathogenic nematodes are an alternative for A. diaperinus control. This study aimed to screen in laboratory entomopathogenic nematodes for A. diaperinus control. Fourteen strains were tested, and for the best LC50 and LC90 was estimated, as well as the control efficiency on adult insects at different temperatures (18, 22, 26, 30 and 35ºC). The poultry litter and sanitary products effect on nematodes were also evaluated. All strains were pathogenic with mortality values varying from 1 to 99%. Steinernema arenarium was the most effective causing 99% mortality. The estimated LC90 was 106 infective juveniles (IJ) per insect (approximately 25 IJ/cm2). No nematodes activity was observed at temperatures above 30°C. The antagonistic action of poultry litter inhibit completely the effect on adult insects and a reduction on larvae control by 57%.